Sociocultural and structural influences on HIV Pre-Exposure Prophylaxis (PrEP) Engagement and Uptake among African American Young adults - Suur D. Ayangeakaa; Jelani Kerr; Ryan M. Combs; Lesley M. Harris; Jeanelle S. Sears; Kimberly Parker; Emma Sterrett-Hong (BMC, 2023)
Abstract Background Pre-exposure prophylaxis (PrEP) demonstrates effectiveness in decreasing new cases of HIV. However, few African Americans use PrEP, despite being disproportionately impacted by HIV. Understanding the influence of sociocultural and structural factors on PrEP use among multiple priority groups of African Americans, including but not limited to men who have sex with men, may improve PrEP engagement and uptake. The social ecological model (SEM) as a framework guided the understanding of how these factors operate on multiple levels to influence PrEP use among this population. Methods This study derived data from the Afya PrEP study consisting of eleven focus groups (N = 63) with 18-29-year-old African American sexual and gender minority and heterosexual individuals at heightened behavioral vulnerability to HIV. We employed constructivist grounded theory processes to inductively analyze the data. A pooled kappa score of 0.90 indicated excellent inter-rater agreement. Results Factors impacting PrEP engagement among African American young adults included: (1) Community/social network influences; (2) medical mistrust; (3) stigma; (4) PrEP availability and accessibility, which had two sub-categories: (a) cost and (b) where to obtain PrEP; and (5) PrEP engagement strategies, which had two sub-categories: (a) current AIDS service organizations' PrEP engagement practices and (b) recommended future PrEP engagement strategies. Categories one through three represent sociocultural factors, and categories four and five represent structural factors that influence perceptions and attitudes of African American young adults regarding PrEP. Conclusion Our study highlights sociocultural and structural factors that act as barriers and facilitators to PrEP engagement. The SEM guided the understanding of how these factors operated on multiple levels. One of the sociocultural factors, community/social network influences operated at the interpersonal level of the SEM; the other two, stigma and medical mistrust, operated at the community level. The structural factors (PrEP availability, accessibility, and engagement strategies) operated at the institutional/organizational level. Thus, multi-level interventions are warranted to improve PrEP engagement among various African American young adult priority groups.